Setting the scene : the deceased and regenerative cult within offering table imagery of the Egyptian Old to Middle Kingdoms, C.2686-C.1650 BC - O'Neill, Barbara (Egyptologist) (Archaeopress Publishing Ltd, 2015)
Ancient Egyptian offering table scenes have been explored from chronological and art historical perspectives over the past century of Egyptological research. This descriptive overview has usually centred on the diachronic evolution of philology and food offerings, focussing less frequently on offering table images as discrete elements of highly codified information. This study investigates gender-based and ritual-dependent afterlife expectations of the deceased over a key phase in Egyptian history from the latter part of the Old Kingdom to the end of the Middle Kingdom Period, c.2686 BC - c.1650 BC. Conclusions indicate that the transformational journey to the afterlife can be understood through a meaningful synthesis of people, produce and ritual embedded within offering table depictions.